POWER RELATIONS IN RELIGIOUS TEACHING SPACES: EXAMINATION OF THE STANDARDIZATION PROGRAM FOR RELIGIOUS PREACHERS IN INDONESIA - Kamaludin, Mohammad; Suyanto, Bagong; Mas'udah, Siti (Sosiohumaniora, 2024)
This research seeks to uncover the issues surrounding the controversy over the implementation of standardization by the Ministry of Religious Affairs of the Republic of Indonesia for Islamic preachers and  teachers in Indonesia. This controversy has been going on for so long that before it was implemented, there  were several changes in the name of the program to avoid polemics in the community. The exchange of discourses between policymakers and policy recipients is interesting to further study. To answer these questions, researchers use research methods that are almost the same as those developed by Foucault, namely Critical Discourse Analysis (CDA. This method emphasizes correcting the discourse that develops in society, especially regarding the standardization program for religious teachers (da'i or ustad). Because religious teachers are also closely related to teaching or da'wah issues. The essence of da'wah is the teaching of the Islamic religion; therefore, this research focuses on the relationship patterns in religious teaching toward other parties related to it. Many studies have been conducted regarding power relations, especially those related to education. However, very few people have studied power relations in religious teaching spaces. This method also develops a way of researching by looking at news in the mass media, where the news produces a certain knowledge that is considered new. Therefore, the researcher collected data in three ways: media observation, interviews with actors, and documentation. According to the researcher, these three methods represent the same method used by Michel Foucault. The findings produced by researchers are three factors that influence the dynamics of power relation patterns. First, power/knowledge relations are produced by several parties. Second, the government has a strong interest in the implementation of the standardization program for religious preachers. Third, the political motive isalmost clearly seen. Penelitian yang dilakukan ini berusaha mengungkap persoalan di seputar kontroversi penerapan standardisasi oleh kementerian agama Republik Indonesia terhadap para penceramah atau pengajar agama Islam di Indonesia. Sudah lama kontroversi ini berlangsung sehingga sebelum sempat diterapkan telah terjadi beberapa kali perubahan nama program demi menghindari polemik di masyarakat. Saling tukar wacana antara pihak pembuat kebijakan dan penerima kebijakan menarik untuk diteliti lebih jauh. Guna mendapatkan jawaban atas pertanyaan tersebut peneliti menggunakan metode penelitian yang hampir sama dengan yang dikembangkan Foucault yakni Analisis Wacana Kritis atau lebih dikenal dengan CDA (Critical Discourse Analysis). Metode ini menekankan pada pengkoreksian wacana yang berkembang di masyarakat terutama soal program standardisasi terhadap para pengajar agama (da’i atau ustad). Metode ini juga mengembangkan cara meneliti dengan melihat pemberitaan di media massa, dimana pemberitaan itu menghasilkan pengetahuan-pengetahuan tertentu yang dianggap baru. Karenanya peneliti mengumpulkan data melalui tiga cara ; observasi media, wawancara dari para aktor dan dokumentasi. Ketiga cara ini menurut peneliti sudah mampu mewakili cara yang sama dilakukan Michel Foucault. Temuan yang dihasilkan oleh peneliti adalah menemukan tiga faktor yang memengaruhi terjadinya dinamika pola relasi kuasa. Yakni transparansi, komunikasi, dan politisasi.